Persuasion, facilitation… contestation? - Lindemer, August (2019)
The causes and consequences of climate change are to varying degrees understood, produced and faced by various societies across the planet. The projected scope of its consequences and the underdetermination thereof causes much public contestation. Scholars of climate change communication express various positions towards the nature of the issue and the purpose of science communicative efforts. Through a literature review of research articles on climate change communication published between 2010 and 2018, I show that top-down approaches to communication based on psychological considerations are frequently argued to provide the necessary response to public uncertainty and disagreement on the issue. Linking these, and other, positions to epistemological and political considerations, I offer a liberal democratic critique of this conception of climate change communication as both ideologically and pragmatically questionable.